Produk Sarawak Menang Anugerah Khas - Saiful Bahari, Hj Mohd Yusoff; Ibrahim, Zalina (Suara Sarawak, 2019)
Smart Knock-down Fish Farming Product has won two awards. One Gold Award at the Seoul International Invention Fair 2019, South Korea and a special award, Thailand Award for the Best International Invention & Innovation in Seoul International Invention Fair 2019, South Korea